Design for adaptability in mass timber: a survey-based analysis of stakeholder roles, digital tools, and decision-making flow - Hasani, Nastaran; Riggio, Mariapaola (Frontiers in Built Environment, 2025)
Carbon sequestration benefits of mass timber (MT) buildings are maximized when their lifespan is extended. Designing MT buildings that are durable and capable of future adaptation is recognized as a direct strategy for prolonging carbon storage before end-of-life interventions are undertaken. Previous studies have identified criteria for flexible design mostly through theoretical research and not specifically for MT. No research has examined whether, and how, adaptability-related decisions are made in real-world MT project workflows. This study builds on an earlier work by mapping these processes. It identifies who makes critical decisions, when in the project timeline it occurs, and which digital tools are used. We conducted a global questionnaire survey of MT stakeholders, analyzing 106 responses. Four criteria emerged as most important overall: structural grid configuration, standardization and compatibility, modularity and scalability, and the location of building cores and services. The schematic design and construction documentation phases were critical decision points, yet certain disciplines were not engaged when their input was required. A convergent design approach that brings all the key actors together is essential at key points, with particular emphasis on the role of MT manufacturers/fabricators. Parametric and simulation workflows, which support stakeholders in co-evaluating adaptability and other design objectives simultaneously, were rarely adopted. However, they can support rapid iteration, real-time feedback in design exploration, and when coupled with analysis and simulation tools, can accelerate progress from schematic design to fabrication drawings. The outcomes of this study can be used to inform future strategies for improving early-stage collaboration and tool interoperability in support of adaptable MT design.